Pengaruh Service Quality, Brand Image dan Perceived Value sebagai Moderating Variable terhadap Brand Loyalty - Siti Rozinah (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2018)
Higher education is one of the service industries that must have service quality and good branding in order to be able to face competition. Higher education institutions must be able to know the condition of service quality, brand image and perceived value obtained by students, so that they will be able to know the effect on brand loyalty. This research was conducted to illustrate the influence of service quality, brand image and perceived value on brand loyalty of Trisakti STMK students. Respondents from this study were 124 STMK Trisakti students. Descriptive analysis is done to find out what factors influence brand loyalty. The results showed that: 34.9% variation in perceived value can be explained by the variables of service quality and brand image, and 64.1% explained by other variables not found in this study, and 48.1% of variables brand loyalty can be explained by variables brand image and perceived value and 51.9% are explained by other variables not found in this study.